Pengelolaan Perilaku Disiplin Belajar Siswa Di Sma Negeri 1 Sukoharjo - Soediatama, Pitaja (2016)
This study aimed to describe: 1) Rule of learning discipline behavior of student at Senior High School State 1 Sukoharjo, 2) implementation of learning discipline behavior of student at Senior High School State 1 Sukoharjo. The research is a a qualitative research with using case studies. Location of this research at Senior High School State 1 Sukoharjo. Subjects in this study are, headmaster and teachers. Data collection techniques performed by the method of interview, observation and documentation. Data analysis technique using interactive model analysis. The results showed that 1) Rule of learning discipline behavior of student at Senior High School State 1 Sukoharjo set in school program, is in a self-development program, both programmed and not programmed and also student's ethic codes. Programmable self-development activities include counseling and extracurricular, while those not programmed include routine activities, spontaneous, and exemplary. Creating 4S culture (Smiles, Regards, Greets and Manners). 2) implementation of learning discipline behavior of student at Senior High School State 1 Sukoharjo occurs with exemplary principles and support of various aspects. Exemplary principals, teachers, Guidance and Counseling teacher and religious teachers largely determines the success of learning discipline students. Section of student held a variety of activities, both routine and incidental. monitoring student teachers and the application of punishment for students who violate the school rules.